Size-dependent interaction of plasma with anatase TiO 2 nanoparticles - Asgharizadeh, Saeid; Khorram, Sirous; Lazemi, Masoud; Hosseinzadeh, Alireza; Malfois, Marc (Physical chemistry chemical physics : PCCP, 2020)
We study the particle size distribution and phase changes of the anatase TiO 2 nanopowder samples when they are subject to the plasma treatments of three different kinds of gases as nitrogen (N 2 ), oxygen (O 2 ), and argon (Ar). The plasma gas pressures vary as 0.1, 0.3, and 0.6 Torr. We demonstrate that the plasma treatments have an effect neither on the phase structure nor on the mean nanocrystalline size. The phase and size invariances of the samples are attributed to their nanoscale thermodynamic aspects. We find out that elevating the gas pressure in some cases creates fine-size amorphous nanoparticles with a narrow distribution. Our findings authenticate that plasma treatment affects the amorphous phase with etching particles down to a mean value of ∼3 nm. The small-angle X-ray scattering (SAXS) technique was utilized to obtain the size distribution of the nanoparticles, and the wide-angle X-ray scattering (WAXS) technique was used to probe the phase and size changes of the crystalline structure.